Jom Masuk U 2024 starts a series of tours to 10 zones nationwide - Nor Salwana, Mohammad Idris (UMPSA, 2024)
PERAK, 3 May 2024 - The Jom Masuk U 2024 Programme (JMU2024) began a series of tours to ten zones throughout the country from 3 May to 9 June 2024 with the opening ceremony completed by the Minister of Higher Education, Yang Berhormat Dato’ Seri Diraja Dr. Zambry Abd Kadir at Universiti Teknologi MARA (UiTM) Perak Branch, Seri Iskandar Campus recently.